Perception of face-to-face and virtual educational environment during COVID-19 pandemic: Medical undergraduates’ experiences in Northern Borneo - Farhana Harzila Mohd Bahar; Jamilah Al-Muhammady Mohammad; Fairrul Kadir; Fatimah Ahmedy; Mohammad Saffree Jeffree; Muhamad Saiful Bahri Yusoff (Penerbit Universiti Sains Malaysia, 2024)
Positive educational environments foster comfort, well-being, academic achievement and collaboration among students, teachers and organizations, supporting the production of quality graduates. Consequently, educational organizations must evaluate their educational environments. This study explores the conditions of the physical and virtual educational environment at Universiti Malaysia Sabah (UMS). A cross-sectional study involving 456 medical students from year one to year five at the Faculty of Medicine and Health Sciences (FMHS), UMS was conducted. Students’ perceptions of their educational environment were assessed using the shortened Dundee Ready Education Environment Measure (DREEM-17) and Online Student Connectedness Survey (OSCS) questionnaires. Quantitative analysis was performed using Statistical Package for Social Sciences (SPSS) version 28. Ethical clearance was obtained from the Human Research Ethics Committee at UMS. In total, 329 out of 456 medical students completed the questionnaires in this study. Students’ perceptions of the physical educational environment were mainly positive, with a mean score of 2.93 (SD = 0.76), while their perceptions of online connectedness in virtual learning were moderate, with a mean score of 2.60 (SD = 0.79). There was no significant difference in students’ perceptions of physical and virtual educational environments based on sex, but there was a notable difference between preclinical and clinical year students, with the latter having less favorable perceptions of virtual education. The preference for physical or blended learning over fully online learning was evident. The low level of perceived support for students’ well-being suggests a need for improvement in support systems in the FMHS, UMS.